PRODUCTION OF HIGH TITRE ANTISERA IN RABBITS AGAINST CLOSTRIDIUM PERFRINGENS BETA AND EpSILON TOXOIDS - Rahman, M S; Rahman, M M (Biological Sciences - PJSIR, 2001)
To investigate the validity of production of high titre antisera against Clostridium perfringens beta and epsilon toxoids in rabbit, the immune response of these toxoid inoculated rabbits were measured. The highest neutralizing antibody titres from the beta and epsilon toxoids were equally 1.50 ± 0.042 on 21st day post-inoculation of toxoid. The precipitating antibodies were detected by agar gel immunodiffusion test on the above mentioned period. Statistically significant (P<O.Ol) rise of antibody titre was observed from 14th day to 21st day post-inoculation of toxoid. Antibody production did not vary significantly due to interaction between day of inoculation and toxoid. It sug- gested the utility of rabbit for excellent production of high titre antisera against Clostridium perfringens beta and epsilon toxoids. ’